En los umbrales de la Instrucción de Titu Cusi Yupanqui - Cattan, Marguerite (2011)
This article provides a detailed discussion of events prior to the writing of the Instrucción al licenciado don Lope García de Castro (1570). It reconsiders the historical events and political maneuvering that lead to the composition of the Instrucción in order to identify the possible interests and motivations behind this manuscript and the objectives pursued by it. It also includes a chronological table of the available documentation